Peran Guru Akidah Akhlak Dalam Pembinaan Karakter Siswa - Syarifah, Muhimmatus; Budiyono, Ahmad; Sapto Hudoyo, Ahmad; Nurbaiti, Siti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The role of Akidah Akhlak teachers is to make all religious efforts to develop religious potential in order to achieve the objectives of Islamic Education, namely to develop students' religious potential to become good people with good character, time discipline, and a sense of responsibility. This article describes the role of Akidah Akhlak teachers in character building of students at MTs Thoriqul Huda Catakgayam Mojowarno Jombang. This research is qualitative field research, specifically descriptive qualitative research, with data collection techniques including interviews, observation, and documentation. Data analysis was then conducted using descriptive qualitative analysis. The results of the study found that the role of Akidah Akhlak teachers in character building for students includes: setting an example for students, encouraging religious activities, giving advice, and imposing sanctions or punishments on students who violate the rules. The characteristics possessed by MTs Thoriqul Huda students include: religious, disciplined, polite, responsible, fond of reading, and honest. In the process of character building, supporting and inhibiting factors for teachers in building student character were found. Among the supporting factors for Akidah Akhlak teachers in character building are cooperation between Akidah Akhlak teachers and the entire madrasah community. Meanwhile, the hindering factor is the different environments of each student, making it difficult for the madrasah to supervise each student when they are outside the madrasah.